Chemical particulate matter PM10 in the atmosphere of Riohacha - La Guajira Colombia - Doria-Argumedo, Calos Julio; Fagundo-Castillo, Juan Reynerio (Universidad Pedagógica y Tecnológica de Colombia - UPTC, 2017)
Given the importance from the point of view of environmental pollution, which have inhalable particles PM10 in urban environments, and the effects that may arise health depend on the chemical composition of the material consists of particles, this study was conducted with the aim of revealing the chemical composition of atmospheric particles through techniques UV-VIS spectrophotometry and Mass Spectrometry Coupled Plasma source, generated mainly by natural and anthropogenic sources in the city of Riohacha north of Colombia; for that 30 samples of atmospheric particles they were collected by quartz filters on a monthly basis during the period from March to December 2014. PM10 have an average concentration of 52.9 µg / m3 and the highest concentration of soluble ions correspond to Na+ , Cl- , Ca+ 2 and Mg+ 2. The differences between sampling sites were not significant (p > 0.6). 70% of Ca + 2 is not of marine origin, attributed to soil and vehicular traffic and people. Knowing the chemical composition of particulate matter, PM10 is relevant not only from the point of view of atmospheric chemistry, but also on the quality of the air we breathe in cities.